Difference between revisions of "008A Sample Final A, Question 16"
Jump to navigation
Jump to search
(Created page with "'''Question: ''' Solve. <math> \log_6(x+2)+\log_6(x-3) = 1 </math> {| class="mw-collapsible mw-collapsed" style = "text-align:left;" !Foundations |- |1) How do we combine th...") |
|||
(One intermediate revision by the same user not shown) | |||
Line 2: | Line 2: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | !Foundations | + | !Foundations: |
|- | |- | ||
|1) How do we combine the two logs? | |1) How do we combine the two logs? | ||
Line 18: | Line 18: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 1: | + | !Step 1: |
|- | |- | ||
− | |Using | + | |Using one of the properties of logarithms the, left hand side is equal to <math> \log_6( (x + 2)(x - 3)</math> |
|} | |} | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 2: | + | !Step 2: |
|- | |- | ||
|By the definition of logarithms <math> \log_6( (x + 2)(x - 3) = 1</math> means <math> 6 = (x + 2)(x - 3)</math> | |By the definition of logarithms <math> \log_6( (x + 2)(x - 3) = 1</math> means <math> 6 = (x + 2)(x - 3)</math> | ||
Line 30: | Line 30: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 3: | + | !Step 3: |
|- | |- | ||
|Now we do some arithmetic to solve for x. <math> 0 = (x + 2)(x - 3) - 6 = x^2 - x - 12 = (x - 4)(x + 3) </math>. So there are two possible answers. | |Now we do some arithmetic to solve for x. <math> 0 = (x + 2)(x - 3) - 6 = x^2 - x - 12 = (x - 4)(x + 3) </math>. So there are two possible answers. | ||
Line 36: | Line 36: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Step 4: | + | !Step 4: |
|- | |- | ||
|We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is <math> (0, \infty)</math> , -3 is removed as a potential answer. | |We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is <math> (0, \infty)</math> , -3 is removed as a potential answer. | ||
Line 42: | Line 42: | ||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
− | ! Final Answer: | + | !Final Answer: |
|- | |- | ||
| x = 4. | | x = 4. |
Latest revision as of 23:02, 25 May 2015
Question: Solve.
Foundations: |
---|
1) How do we combine the two logs? |
2) How do we remove the logs? |
Answer: |
1) One of the rules of logarithms says that |
2) The definition of logarithm tells us that if , then |
Solution:
Step 1: |
---|
Using one of the properties of logarithms the, left hand side is equal to |
Step 2: |
---|
By the definition of logarithms means |
Step 3: |
---|
Now we do some arithmetic to solve for x. . So there are two possible answers. |
Step 4: |
---|
We have to make sure the answers make sense in the context of the problem. Since the domain of the log function is , -3 is removed as a potential answer. |
Final Answer: |
---|
x = 4. |